Un modelo de situación problema para la evaluación de competencias matemáticas (2019)
A problematic situation is a space for questions to be solved by a subject. In the field of mathematics, it is interpreted as a pedagogic space that allows the conceptualization, the symbolization, and the comprehensive application of logarithms in order to propose and solve problems about mathematics, definition that has as a starting point the definitions about what a problem is, according to Piaget, Polya and Garret, among others. In this article, the author presents a theoretical description of the model for problematic situations, proposed by Doctor Orlando Mesa, and the categorizations of the mathematic competences defined with the respective aim indicators by the researcher team in the project MODELS OF PROBLEMATIC SITUATIONS FOR THE MOVILIZATION OF MATHEMATIC COMPETENCES IN THE BASIC FORMATION AT UNIVERSIDAD DE MEDELLÍN, where some new definitions are highlighted, and different tools the evaluation of competences, are applied.